2020
DOI: 10.3390/biology9110390
|View full text |Cite
|
Sign up to set email alerts
|

Lymphotropic Viruses: Chronic Inflammation and Induction of Cancers

Abstract: Inflammation induced by transcription factors, including Signal Transducers and Activators of Transcription (STATs) and NF-κB, in response to microbial pathogenic infections and ligand dependent receptors stimulation are critical for controlling infections. However, uncontrolled inflammation induced by these transcription factors could lead to immune dysfunction, persistent infection, inflammatory related diseases and the development of cancers. Although the induction of innate immunity and inflammation in res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 134 publications
0
5
0
Order By: Relevance
“…From dockinǵs result (Tables S2–S12), we determined the main amino acids in NRP1 to interact with the ten compounds, these are Tyr297, Asn300, Trp301, Thr316, Gly318, Glu319, Asp320, Ser321, Arg323, Glu348, Lys351, Tyr353, Trp411, Thr413 and Gly414 for N1 – N10 compounds, and for EG00229 and EG01377 the amino acids: Tyr297, Trp301, Gly318, Asp320, Glu348, Thr349, Lys351, Thr413 and Ile415 ( Table 2 ). It is reported that Asp320 is very important for NRP1 to interact with different ligands and VEGF-A, 29 , 33 as well as for the CendR region in HTLV-1 18, 22 , 23 and the SARS-CoV-2, 17 which is present in the analyzed interactions.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…From dockinǵs result (Tables S2–S12), we determined the main amino acids in NRP1 to interact with the ten compounds, these are Tyr297, Asn300, Trp301, Thr316, Gly318, Glu319, Asp320, Ser321, Arg323, Glu348, Lys351, Tyr353, Trp411, Thr413 and Gly414 for N1 – N10 compounds, and for EG00229 and EG01377 the amino acids: Tyr297, Trp301, Gly318, Asp320, Glu348, Thr349, Lys351, Thr413 and Ile415 ( Table 2 ). It is reported that Asp320 is very important for NRP1 to interact with different ligands and VEGF-A, 29 , 33 as well as for the CendR region in HTLV-1 18, 22 , 23 and the SARS-CoV-2, 17 which is present in the analyzed interactions.…”
Section: Resultsmentioning
confidence: 97%
“…The neuropilin-1 (NRP1) is a multifunctional protein on the cell membrane, with an impact on physiological functions and diseases in the human organism, 16 , 18 , 19 , 20 , 21 , 22 , 23 for which for more than 20 years specific molecules have been developed that can inhibit/regulate some of its functions, 20 , 24 , 25 , 27 , 28 , 29 , 30 , 31 but they are still developments today and the NRP1 continues to demonstrate new signals/functions, which need further investigation. Therefore, the role of NRP1 in the infectious process of COVID-19 has taken on greater relevance, 16 , 32 since by being able to limit these functions on COVID-19, they could generate a disease with less impact on the human organism and this could help the immune system and being able to alter as it is known today, the natural history of the COVID-19 disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also known that LMP1 functions as an inflammation-promoting factor, at least by inducing a panel of pro-inflammatory cytokines, such as TNFα, IL6, IP10, among many others, via NFκB, AP1, and STAT3 [174][175][176]. Activation of NFκB and AP1 by LMP1 also induces miRNAs including miR-155, miR-146a, and miR-21, which play key roles in the regulation of inflammation [177][178][179].…”
Section: Lmp1 Promotes Chronic Inflammation and The Tumor Microenvironmentmentioning
confidence: 99%
“…These viruses are generally transmitted by the fecal-oral route and show strong tissue tropism to small intestinal epithelial cells, causing diarrhea [7]. Recent studies demonstrated that some of these enteric viruses, along with gammaherpesvirus members, EBV, may also play an essential role in the induction of gut inflammation leading to cancer [8]. In this comprehensive review, we have thoroughly discussed critical studies and recent scientific updates that link the pathological functions of viruses associated with gastric inflammation and cancer.…”
Section: Introductionmentioning
confidence: 99%